Nickel-catalyzed electrochemical reductive decarboxylative coupling of N-hydroxyphthalimide esters with quinoxalinones. Issue 97 (21st November 2019) - Lian, Fei; Xu, Kun; Meng, Wei; Zhang, Haonan; Tan, Zhoumei; Zeng, Chengchu
Abstract : The first example of electrochemically enabled, NiCl2 -catalyzed reductive decarboxylative coupling of N -hydroxyphthalimide esters with quinoxalinones was developed. Abstract : Herein the first example of electrochemically enabled, NiCl2 -catalyzed reductive decarboxylative coupling of N -hydroxyphthalimide (NHP) esters with quinoxalinones is reported. A range of primary, secondary, tertiary aliphatic carboxylic acids and amino acid-derived esters were tolerated well. This decarboxylative coupling allows access to structurally diverse 3-alkylated quinoxalinones in up to 91% yields.